George Washington, man of courage and prayer - Camp, Norma Cournow; Manderfield, Diane (Milford, Mich. : Mott Media, 1977)
Examines George Washington's religious beliefs and attitude towards God as reflected in his diaries and letters.
Bibliography: p. [165]
Includes index.
Keywords: Washington, George, -- 1732-1799 -- Religion -- Juvenile literature; Presidents -- United States -- Biography -- Juvenile literature; Washington, George, -- 1732-1799 -- Religion; Presidents